Enhancing Students’ Speaking Proficiency Through Storytelling Method at Education College of Togo Ambarsari Bondowoso - Henny Merizawati; Ahmad Munawir; Indah Sulita; Syaadiah Arifin; Muta’allim (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
The use of the storytelling method at STITTA Bondowoso is investigated to measure its effectiveness in improving the English speaking skills of students. This research aims to examine the enhancement of students' speaking abilities through the implementation of the Storytelling method. The study falls under the category of qualitative research. The data in this study consist of students' storytelling discourse, with the data source being students enrolled in English courses at STITTA Bondowoso. The method used to collect data is the observe-participate-transcribe method. The researcher observed the context of English language learning in the classroom, particularly related to the Storytelling method. Additionally, interviews were conducted with English language instructors, students, and relevant parties at STITTA regarding the implementation and impact of the Storytelling method on improving students' speaking abilities, supplemented with recording and note-taking techniques. The collected data were then reduced and classified based on their types. Subsequently, data analysis and in-depth interpretation were conducted. The research results indicate that 1) STITTA students experience a significant improvement in speaking abilities in English learning; 2) students feel happy, enthusiastic, and entertained in learning English; 3) students are motivated to compete in English learning; and 4) students are eager to compete for achievements. The findings of this research demonstrate a positive correlation between the use of storytelling techniques and the improvement of students' speaking abilities. The depth and inherent appeal in the storytelling process not only enhance language retention but also create a more interactive and dynamic learning environment. The implications of this research have broad impacts, involving language educators, curriculum developers, and policymakers. This research emphasizes the urgency of integrating innovative methods and experiences to enhance speaking abilities in the context of language education. The contribution of this research lies in strengthening the discourse on effective language pedagogy, emphasizing the importance of adopting diverse and interactive teaching strategies to meet the evolving needs of students in the language learning process.